1981
DOI: 10.3109/00016488109138538
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinthine Barriers and Cochlear Homeostasis

Abstract: The blood-labyrinth barrier is a concept used to explain the stability of composition of the labyrinthine fluids in spite of systemic alterations in blood composition. This blood-labyrinth barrier concept was tested by injecting various test substances into the systemic circulation of experimental animals and recovering these compounds in perilymph. The concentration of each test substance in perilymph lagged behind that of serum, and the transport of a series of test substances was found to be inversely relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(86 citation statements)
references
References 7 publications
1
83
0
2
Order By: Relevance
“…Direct delivery to the fluids of the inner ear is necessary because of the presence of a blood-labyrinth drug barrier, which is anatomically and functionally similar to the blood-brain barrier [20,21]. Direct delivery also has significant potential advantages for therapeutic application.…”
Section: Discussionmentioning
confidence: 99%
“…Direct delivery to the fluids of the inner ear is necessary because of the presence of a blood-labyrinth drug barrier, which is anatomically and functionally similar to the blood-brain barrier [20,21]. Direct delivery also has significant potential advantages for therapeutic application.…”
Section: Discussionmentioning
confidence: 99%
“…Direct delivery to the fluids of the inner ear is necessary because of the presence of a bloodlabyrinth drug barrier, which is anatomically and functionally similar to the blood-brain barrier [19,20]. Direct delivery also has significant potential advantages for therapeutic application.…”
Section: Introductionmentioning
confidence: 99%
“…Noise-triggered damage leads to impairment of the stereocilias of the hair cells, the loss of hair cells, and structural distortion at the spiral ligament and spiral ganglion [2,3] . It was reported that hair cells become dysfunctional within 2 weeks after noise exposure, and an edema develops in the spiral ganglion neurons [4,5] . Nevertheless, the molecular mechanisms of noise-induced hearing loss are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%